Population of bagworms (Metisa plana) on different level strata of oil palm / Shah Izlan Jamal - Jamal, Shah Izlan (Faculty of Plantation and Agrotechnology, 2018)
The bagworm in Malaysia are the leaf-eating insect pest that can give high impact losses to their host plant, oil palm. The aim of the study to determine the population of bagworm at different strata of oil palm frond. This study was carried at FELDA Technoplant Plantation Trolak Selatan division which has been seriously attack by bagworm. The data of bagworm population for every strata of oil palm frond were collected from this study area. It also include detail information about the oil palm tree and information about the site of the study to use as the references. This study was carried out from January 2018 until December 2018. Result from the analysis showed high number of bagworm population were found at the lower strata and the lower population of bagworm found at upper strata. Different in population of bagworm at every strata cause by several factor such as the arrangement of lower fronds connecting to fronds of other oil palm tree, lower strata less expose to the sunlight and nutrient content on the frond leaves at lower strata.